INTERNALIZATION OF HUMAN VALUES IN THE LEARNING PROCESS PANCASILA EDUCATION AT SMP NEGERI 3 PANGKAJENE: Internalisasi Nilai Kemanusiaan dalam Proses Pembelajaran Pendidikan Pancasila di SMP Negeri 3 Pangkajene - Budiman Mustafa; Mustaring; Bakhtiar (SOSIOEDUKASI, 2026)
This study aims to analyze the internalization of humanitarian values in the Pancasila Education learning process at SMP Negeri 3 Pangkajene, focusing on learning activities, supporting and inhibiting factors, and the dynamics of pedagogical interaction between teachers and students. This study employs a descriptive qualitative approach. Data were collected through observation, interviews, and documentation. The data analysis was conducted interactively through data reduction, data display, and conclusion drawing to reveal the contextual process of value internalization. The findings indicate that the internalization of humanitarian values has been implemented through discussions, reflections, and the use of technology-based learning. However, the process has not been fully optimal as it is still predominantly oriented toward cognitive aspects. Low student participation in critical discussions, limited contextual learning strategies, and weak integration of values into instructional content are identified as the main inhibiting factors. On the other hand, teacher role modeling, dialogical approaches, and the use of active learning methods serve as key supporting factors in strengthening the internalization process. This study highlights that the effectiveness of humanitarian value internalization is strongly influenced by the quality of pedagogical interaction and the teacher’s ability to contextualize values into students’ real-life experiences. Therefore, Pancasila Education learning needs to be reoriented from mere knowledge transmission toward transformative learning that is based on experience and value reflection